Analysis of a series of Italian APECED patients with autoimmune hepatitis and gastro-enteropathies - Paldino, Giorgia; Faienza, Maria Felicia; Cappa, Marco; Pietrobattista, Andrea; Capalbo, Donatella; Valenzise, Mariella; Lampasona, Vito; Cudini, Annamaria; Carbone, Elena; Pagliarosi, Olivia; Maggiore, Giuseppe; Salerno, Mariacarolina; et al. (Frontiers in Immunology, 2023)
Introduction Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) syndrome is a rare monogenic disease determined by biallelic mutations in AIRE gene, which encodes a transcription factor essential for central immune tolerance. Classic diagnosis is determined by the presence of two of the main APECED clinical diseases: chronic mucocutaneous candidiasis, chronic hypoparathyroidism, and Addison’s disease. Non-endocrine autoimmunity, involving the liver, intestine, eyes, and kidneys, is generally reported in a minority of European patients, while American APECED patients have a higher tendency of developing organ-specific non-endocrine manifestations early in life. This observation led to the revision of the diagnostic criteria to permit earlier diagnosis based on the appearance of one classic triad symptom or one non-classical manifestation at a young age in the presence of IFNωAbs or AIRE mutations (Ferre-Lionakis criteria). Patients and methods We analyzed the clinical, genetic, and autoantibody (Ab) profiles in a series of 14 pediatric Italian APECED patients with gastrointestinal manifestations (seven male and seven female patients). Ten patients presented hepatitis (APECED-associated hepatitis (APAH)), while seven were affected by constipation, diarrhea, and malabsorption. Four patients had developed APAH before classic triad symptoms. Results Based on the age of appearance of non-endocrine manifestations including APAH and gastro-enteropathy, the Ferre-Lionakis criteria would have allowed an expedited diagnosis in 11/14 patients. Abs to tryptophan hydroxylase (TPHAb) and hepatic aromatic l-amino acid decarboxylase (AADC) were significantly associated with APECED patients of the present series. Abs to cP4501A2 were detectable in the serum of 4/8 patients with APAH, and Abs to cP4502A6 were detectable in 3/8 patients. AADC Abs tested positive in 5/7 patients, which is indicative of gastrointestinal dysfunction in APECED and TPHAb in 5/7 patients with gastrointestinal dysfunction. IFNAb was significantly associated with the syndrome. Conclusion Although Ferre-Lionakis expanded criteria applied to the American cohorts of APECED patients would require validation in independent large cohorts of European patients, the results of this study emphasize the importance to evaluate the presence and the age of appearance of APAH and autoimmune enteropathy even in European cohorts for an earlier APECED diagnosis. An earlier APECED diagnosis would also allow the prevention of episodes of life-threatening hypocalcemic seizures and adrenal crisis, which are the main manifestations of undiagnosed APECED.